Accessibility of public library Web sites - Golub, Koraljka (2002)
As libraries are intended to provide equal access to information for all, our intention was to determine to what extent Croatian public libraries really ensure access to content provided on their Web pages. To that purpose, W3C&#8217 ; s Web Content Accessibility Guidelines 1.0 have been used to compare the sites with the recommended guidelines. Libraries should provide accessible Web sites, as well as promote Web content accessibility in the community.